Metachronous Liver Metastasis from Alpha-Fetoprotein-Producing Gastric Cancer Successfully Treated with Capecitabine/Oxaliplatin Combination Chemotherapy - Soichi Furukawa; Takashi Kobayashi; Saori Shiono; Shuta Nishinakagawa (Case Reports in Surgery)
A consensus regarding the treatment of recurrent alpha-fetoprotein-producing gastric carcinoma due to its rarity is lacking. We herein describe a case of such a carcinoma that was associated with metachronous liver metastasis. A 73-year-old man was referred for the surgical treatment of a type 2 gastric tumor that extended from the greater curvature of the gastric corpus to the pylorus. As no remote metastases were detected, the patient underwent open total gastrectomy with lymphadenectomy and Roux-en-Y reconstruction. Histopathological examination revealed regional lymph node metastasis and the invasion of the muscularis propria by a moderately differentiated adenocarcinoma. Immunostaining of the primary tumor was positive for alpha-fetoprotein and negative for human epidermal growth factor receptor 2. Serum alpha-fetoprotein levels decreased to within normal limits after eight courses of S-1 monotherapy; however, levels started to increase, and a hypovascular nodule in segment 5/6 of the liver was detected 3.5 years later. Serum alpha-fetoprotein levels returned to the normal range, and the tumor was undetectable after four courses of capecitabine and oxaliplatin therapy. No recurrence was detected at 1.5-year follow-up. This case demonstrates that combined capecitabine and oxaliplatin therapy can successfully treat metachronous liver metastasis from alpha-fetoprotein-producing gastric carcinoma.